Traditional Knowledge and Traditional Cultural Expressions as Communal Intellectual Property: Are They Protected Under the WIPO Treaty on Intellectual Property, Genetic Resources, and Associated Traditional Knowledge 2024? - Putu Aras Samsithawrati; Ni Ketut Supasti Dharmawan; Made Aditya Pramana Putra; Dewa Ayu Dian Sawitri (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
Indonesia has a culture and natural wealth that has the potential to be protected by Communal Intellectual Property (CIP). Indonesian national law has shown seriousness in the legal protection of CIP by issuing various CIP laws and regulations. However, the protection of CIP at the international level has only appeared with the issuance of the WIPO Treaty on Intellectual Property, Genetic Resources and Associated Traditional Knowledge GRATK/DC/7 2024 (WIPO Treaty GRATK/DC/7 2024) 2024. This paper examines the protection of Traditional Knowledge (TK) and Traditional Cultural Expressions (TCE) as CIP in Indonesia and internationally through the WIPO Treaty GRATK/DC/7 2024. The normative legal research method is used with a statutory, conceptual, comparative and analytical approach. The results show that PP 56/2022 and Permenkumham 13/2017 provide sufficient protection for CIP works including TK and TCE, especially in the form of defensive protection (inventory and recording of CIP). WIPO Treaty GRATK/DC/7 2024 emphasizes genetic resources (GR) protection and TK related to GR and not TCE. However, TCE protection internationally is seen in the amendment to the Berne Convention, Article 15.4 through